Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1002/ptr.2521
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2‐mediated induction of detoxifying enzymes by alantolactone present in Inula helenium

Abstract: Our previous study showed that a methanol extract of Inula helenium had the potential to induce detoxifying enzymes such as quinone reductase (QR) and glutathione S-transferase (GST) activity. In this study the methanol extract was further fractionated using silica gel chromatography and vacuum liquid chromatography, to yield pure compounds alantolactone and isoalantolactone as QR inducers. Alantolactone caused a dose-dependent induction of antioxidant enzymes including QR, GST, gamma-glutamylcysteine synthase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 26 publications
(25 reference statements)
2
35
0
2
Order By: Relevance
“…Alantolactone also stimulated the nuclear accumulation of Nrf2 that was inhibited by phosphatidylinositol 3-kinase (PI3K) inhibitors. In conclusion, alantolactone appears to induce detoxifying enzymes via activation of PI3K and JNK signaling pathways, leading to translocation of Nrf2, and subsequent interaction between Nrf2 and ARE in the encoding genes (Seo et al, 2008). Grosheimin (264), isolated from the medicinal plants of Youngia japonica, exhibited strong antiallergic and antioxidant activities (Yae et al, 2009).…”
Section: Other Activitiesmentioning
confidence: 99%
“…Alantolactone also stimulated the nuclear accumulation of Nrf2 that was inhibited by phosphatidylinositol 3-kinase (PI3K) inhibitors. In conclusion, alantolactone appears to induce detoxifying enzymes via activation of PI3K and JNK signaling pathways, leading to translocation of Nrf2, and subsequent interaction between Nrf2 and ARE in the encoding genes (Seo et al, 2008). Grosheimin (264), isolated from the medicinal plants of Youngia japonica, exhibited strong antiallergic and antioxidant activities (Yae et al, 2009).…”
Section: Other Activitiesmentioning
confidence: 99%
“…3,4 Our previous study demonstrated that sesquiterpenes isolated from Inula helenium (also known as Elecampane) induced NQO1 (QR), an anticarcinogenic marker enzyme. 5,6 In an attempt to elucidate the underlying mechanism of phase 2 enzyme induction by the sesquiterpene isoalantolactone, the effect of isoalantolactone (Fig. 1) on Nrf2=ARE activation was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Further chromatographic fractionation to search for active component(s) resulted in active fraction (CZ-6) which contains (+)-(3S,4S,5R,8S)-(E)-8-acetoxy-4-hydroxy-3-isovaleroyloxy-2-(hexa-2,4-diynyliden)-1,6-dioxaspiro[4,5]de cane as QR inducer, belonging to acetylene family. Although the fraction showed relatively weak activity in QR induction compared to other known phytochemicals [8,13-16], its QR-inducing potential of the fraction at the 20 µg/mL was compatible with 10 µM tert-butylhydroquinone (tBHQ), a known QR inducer, in BPRc1 cells. Furthermore, its relatively low QR-inducing potential in BPRc1 cells with defective arylhydrocarbon receptor translocator (arnt) indicates that the fraction consists of a mixture of bifunctional inducer and monofunctional inducer.…”
Section: Discussionmentioning
confidence: 99%